Drought alters the functional stability of stream invertebrate communities through time - Catherine Leigh; Thomas W. H. Aspin; Thomas J. Matthews; Robert J. Rolls; Mark E. Ledger (Journal of Biogeography, 2019)
Aim In fresh waters, most biogeographical understanding of how extreme events such as drought modify biodiversity and ecosystem functioning derives from static, spatial comparisons of ecological communities, between intact and disturbed sites or along stress gradients. Impacts of drought on the development of ecological communities over time remain poorly resolved, with information on parallel trends in community structure and function particularly scarce. In theory, drought could progressively eliminate both species and functional traits, rendering communities increasingly taxonomically and functionally nested subsets of their pre‐existing counterparts. Alternatively, drought could create new niche opportunities, producing a continuous turnover of species and traits, or simply constrain natural community succession. Location Dorset, UK. Taxon Aquatic invertebrates. Methods We studied temporal changes in community structure and function in artificial streams over 2 years, comparing drought (frequent drying) with control (constant flow) conditions. Temporal beta diversity was partitioned into turnover and nestedness components, calculated using both presence–absence and abundance data, and analysed using time‐lag and null modelling approaches. Results Community development was comparable taxonomically under control and drought conditions, driven primarily by temporal turnover of species. Under control conditions, corresponding trends in functional composition were not apparent, and species turnover was characterized by the progressive replacement of some species by others of equivalent abundance. By contrast, species turnover in disturbed communities was accompanied by both functional turnover and greater loss of individuals, indicating that new colonists were not equivalent, either functionally or numerically, to those they replaced. Furthermore, functional dissimilarities between time points were greatest under drought, and more similar in magnitude to taxonomic dissimilarities, implying that drying reduced the stability and redundancy of functional attributes. Main conclusion A shift to drier climate could disrupt the natural development of stream community structure, and undermine functional stability, at local and biogeographical scales, with potentially significant consequences for ecosystem services provisioning in fresh waters.